Application of linear programming and optimisation software in an operations consultancy problem : a costs-minimising computerised optimisation model for empty container repositioning. - Wang, Jiali. (2012)
This paper considers the empty container repositioning problem in a multi-vessel, multi- port and multi-voyage shipping network with unbalanced customers’ demand and assumes that repositioning decisions are implemented in a rolling horizon manner. The objective is to minimise the expected total repositioning costs such as day-dependent transport cost, port handling cost (i.e. the costs of loading and unloading an empty container at a port), holding (i.e. storage) cost and lost-sale penalty cost. The AIMMS optimisation software was used to model the linear programming formulation, and generate repositioning solutions for end-user shipping companies. What-If analysis was subsequently conducted to study possible repositioning solutions under different empties demand and supply scenarios.